Radiation Shielding Properties of Oxides (Al2O3, PbO and Fe2O3) based on Klein-Nishina Cross-section - Karki, B.; Dhobi, S. H.; Yadav, K.; Nakarmi, J. J. (Journal of Nepal Physical Society, 2023)
In this study, we investigate the Klein-Nishina differential cross-section equation for total cross-section and extend it to calculate the total molecular cross-section for compounds Al2O3, PbO, and Fe2O3. Our findings reveal that the total molecular cross-section of these compounds is significantly larger, with values 5 times greater than the total atomic cross-section. Furthermore, we determine that the molecular cross-section of Al2O3, PbO, and Fe2O3 is 73, 132, and 118 times greater than the total electronic cross-section, respectively, while the atomic cross-section of these compounds is 15, 66, and 24 times greater. At low energy levels ranging from 1-5 MeV, the entire molecular, atomic, and electronic cross-section dominates due to Compton scattering. However, as the photon energy increases, Compton scattering becomes negligible, and a slight contribution from pair production scattering is observed. We also establish the adequate atomic numbers for Al2O3, PbO, and Fe2O3, which are determined to be 15, 66, and 24, respectively. These results highlight the significance of mass attenuation, cross-section, and adequate atomic number in the selection of radiation shielding materials for various protection purposes. The findings from this study provide valuable insights into the properties and behavior of these compounds, enabling informed decisions in radiation shielding applications.